A novel methodology to determine volcanic aerosols optical properties in the UV and NIR and Ångström parameters using Sun photometry. Issue 18 (18th September 2017) - Sellitto, P.; Salerno, G.; La Spina, A.; Caltabiano, T.; Terray, L.; Gauthier, P.‐J.; Briole, P.
Abstract: Remote volcanic aerosol optical depth (AOD) observations of Mount Etna summit and distal bulk plume have been carried out between 14 and 20 July 2016 in the framework of the EPL‐RADIO project. Ultraviolet (UV) and near‐infrared (NIR) AODs were measured using a Microtops‐II Ozone Monitor (MIIOM) Sun photometer, using a Langley plot (LP) instrumental calibration routine. Ozone‐corrected UV AODs at 320 nm are derived for the first time with a Microtops, thus extending the exploitable spectral band range of portable photometers to shorter wavelengths. The new UV AODs have theoretical uncertainties <±0.035 (±12%), dominated by LP calibration errors. Using UV and NIR AODs, the Ångström coefficients have been derived. The UV AODs and Ångström exponents have been compared, at background conditions, to colocated Cimel Sun photometer observations. A root‐mean‐square deviation of 0.03 (13%) for the UV AOD is found for this comparison, thus in agreement with estimated theoretical uncertainties. The MIIOM Ångström exponent estimations are found consistent with Cimel observations, even if with an average overestimation of 17.5%, mainly due to negative biases (−0.02/−21%) of NIR AODs. Results of quasi‐simultaneous characterization of proximal and distal plume (7 km from craters), for 20 July 2016, are shown. During the measurements, brownish ash puffs were visible. While proximal and distal plumes were observed within approximately 1 h, their Ångström exponent varied significantly (mean values: −0.30±0.22 and 1.16±0.33, for the proximal and distal plumes). These results indicate quick sedimentation of ash particles and show the potential of this new retrieval technique to characterize volcanic aerosols. Plain Language Summary: This paper discusses a new technique to better identify the different particles emitted by a volcano, using very small instruments that can be easily transported (in a small backpack) to a volcano summit. Usually, this is done with big and heavy instruments but it is hard to bring them on a volcano summit, and that is why we study new techniques to better use small portable instruments. This new methodology is applied during a measurement campaign at Etna volcano, carried out between 14 and 20 July 2016. These measurements with small, transportable instruments allowed understanding how bigger ash particles cannot be transported by the winds, once they are emitted by Etna, for longer times than a few minutes and have an impact only for a small region (a few kilometers) around the craters, at least for this specific period of measurements and activity of Etna volcano. On the contrary, small liquid acid particles formed by the condensation of volcanic gas emissions are detected at larger distances and can have an impact on climate (in the case of Etna, up to hundreds of kilometers, well into the Mediterranean basin). Key Points: Microtops‐II Ozone Monitor is used for the first time to determine ozone‐corrected UV (320 nm) volcanic AOD and UV/NIR Ångström parameters The new volcanic aerosol products have limited random and systematic uncertainties and compare well with colocated Cimel observations Mount Etna distal and proximal plumes are characterized and discussed